What do we mean by wet? Geoarchaeology and the reconstruction of water availability - Jones, Matthew D. (Elsevier, 2012)
Geoarchaeology has a key role to play in the human-climate-environment debate, including research into the controls and variability of water availability. However its interdisciplinarity can cause complications as well as advantages and leads to confusion as to what researchers should be investigating and how they should be reporting their findings. In this paper I investigate Geoarchaeology, and its place in 21st century science, as well as investigating its role in reconstructing past water availability and some of the challenges involved in ensuring these investigations are undertaken in a robust manner that will enhance academic knowledge and debate.